An Evaluation of Pixel-Based Methods for the Detection of Floating Objects on the Sea Surface. (11th February 2010) - Borghgraef Borghgraef, Alexander Alexander; Barnich Barnich, Olivier Olivier; Lapierre Lapierre, Fabian Fabian; Van Droogenbroeck Van Droogenbroeck, Marc Marc; Philips Philips, Wilfried Wilfried; Acheroy Acheroy, Marc Marc
Abstract : Ship-based automatic detection of small floating objects on an agitated sea surface remains a hard problem. Our main concern is the detection of floating mines, which proved a real threat to shipping in confined waterways during the first Gulf War, but applications include salvaging, search-and-rescue operation, perimeter, or harbour defense. Detection in infrared (IR) is challenging because a rough sea is seen as a dynamic background of moving objects with size order, shape, and temperature similar to those of the floating mine. In this paper we have applied a selection of background subtraction algorithms to the problem, and we show that the recent algorithms such as ViBe and behaviour subtraction, which take into account spatial and temporal correlations within the dynamic scene, significantly outperform the more conventional parametric techniques, with only little prior assumptions about the physical properties of the scene.